The Influence of Talent Management on Employee Performance through Job Engagement in Universities in Jinan - Ling, Zhang (UNIMAS, 2025)
University counselors’ role are important in the education support system, and thus prioritizing and optimizing counselors’ talent management are seen as the key link to ensuring better learning and support for students. This study investigates the intricate relationship between talent management, job engagement, and employee performance of university counselors across multiple universities in Jinan, Shandong Province, China. The sample comprises 181 counselors from various universities in the region. Employing a quantitative research methodology, the findings reveal that talent management significantly enhances job engagement and employee performance. Additionally, job engagement positively influences employee performance. Furthermore, job engagement partially mediates the relationship between talent management and employee performance. By thoroughly analyzing these interconnected variables, this research aims to offer valuable insights into the dynamics of talent management strategies and their effects on job engagement and employee performance within the specific context of Jinan. The study enhances understanding of how effective talent management boosts job engagement and employee performance in the local academic context. Keywords:Talent management, job engagement, employee performance